The public perception of facilities maintenance of mosque / Nurul Amirah Hamizah Abdul Hamid - Abdul Hamid, Nurul Amirah Hamizah (2014)
In this dissertation were discussed about the public perception of facilities maintenance of mosque. It will focus on public perception on the level of cleanliness and condition of facilities at the mosque.in this dissertation also discuss about the types of maintenance, types of public facilities, process and procedure in doing maintenance works. Besides, the level of satisfaction of facilities that provides in mosque also discussed in this dissertation where the questionnaire are make and analyse the data to get the information. A literature review identified the types of maintenance, the process and procedures in doing the maintenance work. The method that used in this study is mix method were used quantitative and observation to complete the studies. Data was gathered through the visual observation, and questionnaire. The questionnaire was distributed to the respondent to get the public satisfaction of the condition and cleanliness of facilities at mosque. There are three case study that was held which is in Masjid Sultan Salahuddin Abdul Aziz Shah, Shah Alam, Masjid Ar-Rahimiah, Klang and Masjid Raja Tun Uda, Seksyen 16, Shah Alam. The key finding shows the maintenance that used in each of three mosque. Masjid Negeri is the mosque that has a better maintenance program where used preventive and corrective maintenance. Other than that, in this study also can identify the result level of public perception of facilities maintenance of the mosque. The study was limited to three case studies only in area Selangor. A teach case study was distributed questionnaire, doing observation of facilities provided at mosque. The findings provides a holistic overview of the facilities maintenance at mosque and level of public perception whether its average or not. So,the overall of the study can contribute the recommendation for the future study.